Analisis Penggunaan E-Bekal Terhadap Minat Beli Santri Pondok Pesantren Nurul Jadid - Lailatus Syarifah; Husnah, Dalilatul; Hasanah, Dini Wasilatul (BISMA : Business and Management Journal, 2023)
E-bekal is an electronic currency founded by the Nurul Jadid Islamic Boarding School which is used as a commodity. This research on the use of E-Provisions on students' buying interest uses a quantitative descriptive approach. This research was implemented at the Nurul Jadid Islamic Boarding School because based on the results of initial research observations, the Islamic Boarding School has an electronic payment facility, namely E-Supplies, which can influence students' buying interest. This research uses quantitative methods. Apart from that, the research results show that E-supplies play a constructive and significant role in controlling student spending, with an influence of 83.7%. This shows that the existence of E-supplies can increase students buying interest and can also fulfill their daily needs.